2021
DOI: 10.30625/ijctr.894029
|View full text |Cite
|
Sign up to set email alerts
|

Seyahat ve Turizmde Paylaşım Ekonomisi: Airbnb Türkiye Örneği

Abstract: Küreselleşme süreçleri ve iletişim alanındaki gelişmeler, çağdaş toplumların geleneksel olmayan yeni seyahat alternatiflerini üretmelerine neden olmaktadır. Bu yeni alternatiflerin çoğunlukla, önemli bir olgu haline gelen ve âtıl haldeki mal ve hizmetlerin paylaşım yolu ile ekonomiye kazandırılması olarak tanımlanan, paylaşım ekonomisi temeli üzerinde ortaya konduğu görülmektedir. Airbnb, Uber, ZipCar, Kickstarter ve daha birçoğu paylaşım ekonomisi dünyasında hızla büyüyen öncüleri oluşturmaktadır. Birçok alan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…In our study, it was observed that the probability of using Airbnb decreased with the diminishes in the average number of trips. Young (2021), Lee et al (2021), Avunduk et al (2021) and Mohsin et al (2021), and many other studies, revealed in this study that people want to interact socially with local cultures, want to feel authenticity and experience all aspects of the cultural texture of the region they visit.…”
Section: Tanımlayıcı İstatistiklermentioning
confidence: 52%
See 1 more Smart Citation
“…In our study, it was observed that the probability of using Airbnb decreased with the diminishes in the average number of trips. Young (2021), Lee et al (2021), Avunduk et al (2021) and Mohsin et al (2021), and many other studies, revealed in this study that people want to interact socially with local cultures, want to feel authenticity and experience all aspects of the cultural texture of the region they visit.…”
Section: Tanımlayıcı İstatistiklermentioning
confidence: 52%
“…Airbnb özellikle güvenlik ve mahremiyet açısından otellere göre daha az performans gösterebilmektedir. Ancak maliyet olarak (Avunduk & Akpınar, 2021) daha uygun ve ulaşılabilirlik açısından daha pratik olduğu için insanlar daha fazla tercih etmeye başlamıştır. İnsanlar daha farklı deneyimler yaşamak istedikleri için de Airbnb'ye yönelmiş durumdadırlar (Guttentag vd., 2019).…”
Section: Turizm Endüstrisi Ve Airbnbunclassified